Paraneoplastic Pemphigus Presenting as Mild Cutaneous Features of Pemphigus Foliaceus and Lichenoid Stomatitis with Antidesmoglein 1 Antibodies - Yayoi Niimi; Bungo Ohyama; Giovanni Di Zenzo; Valentina Calabresi; Takashi Hashimoto; Seiji Kawana (Hindawi Limited, 2010)
Herein, we report a case of paraneoplastic pemphigus with mild skin features of pemphigus foliaceus and lichenoid stomatitis associated with B-cell lymphoma. A 49-year-old man presented with scattered blisters and erosions on the trunk along with mucosal blisters and erosions. Skin biopsy showed subcorneal acantholytic bulla and oral mucosal biopsy demonstrated lichenoid dermatitis. Direct immunofluorescence showed cell surface deposits of IgG and C3. Indirect immunofluorescence identified circulating IgG autoantibodies to the cell surfaces of normal human skin and also on the transitional epithelium of rat bladder. Enzyme-linked immunosorbent assay using recombinant baculoproteins showed positive antidesmoglein 1 autoantibodies (index 46) but negative antidesmoglein 3 autoantibodies (index 8). Immunoblot analysis using normal human epidermal extract detected BP230 and the 190 kDa periplakin, while immunoprecipitation using radiolabeled cultured keratinocyte immunoprecipitated BP230 and the 210 kDa envoplakin. We consider that the skin lesion was produced by humoral immunity whereas the oral lesion was produced by cellular immunity.